Market Demand Mediates the Impact of Product Quality and Innovation on Entrepreneurial Performance - Heny Ratnaningtyas; Michael Khrisna Aditya; Alda Chairani; Pricilia Johani Sakti; Haryo Wicaksono (University of Merdeka Malang, 2025)
Market demand plays a crucial role in mediating the relationship between product quality, innovation, and entrepreneurial performance. Understanding how market demand influences this dynamic is essential for business owners to strategically enhance their competitiveness and long-term success. This research aims to examine the impact of product quality and product innovation on the performance of clothing convection business owners through market demand in home industries in Jurangmangu. Given the large sample size, path analysis is employed to assess both direct and indirect effects. The research population consisted of 215 home industry clothing business owners in Jurangmangu, with a sample size of 168 participants. The findings indicate that: (1) Product quality and product innovation directly affect market demand; (2) Product quality and product innovation have a direct effect on the entrepreneurial performance of business owners; (3) Market demand significantly influences entrepreneurial performance; (4) Product quality and product innovation do not indirectly affect entrepreneurial performance through market demand. High-quality products increase consumer satisfaction, foster brand loyalty, and contribute to long-term business growth. Innovative products, including creative designs and advanced production technologies, capture emerging trends and highlight local culture, offering a competitive advantage even in the face of challenges such as environmental pests.